(untitled) (American Journal of Technology and Applied Sciences, 2024)
At present, in the design and construction of settlements, industrial enterprises, transport communications, canals and other structures, along with traditional design methods (analytical, graphic, model-graphic, layout-graphic), automated design systems based on the use of digital terrain models (DTM) are increasingly used. It is the DTM that is the source material for the operation of computer-aided design systems (CAD) for construction and automated control systems (ACS). The use of DTM significantly simplifies and accelerates many processes of urban management, from calculating areas to compiling lists of tax defaulters.